Why the Folks of Dostoevsky’ first novel are Poor - Karen A. Stepanyan (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2018)
The first Dostoevsky's novel "The Poor Folk" is analyzed in this article as an artistic representation of tragic dissociation of people and discord between the conscious and unconscious in a person's heart. The article covers Dostoyevsky's world view in the course of writing his first novel, ways of presentation the author's point of view in it; also we follow the origins of Dostoyevsky's creative method, prove that the novel belongs to realistic sentimentalism and explain this new term.